Animating Indonesian folklore “Smong” as a child-friendly guide for disaster preparedness - Agung Zainal Muttakin Raden; Muhammad Iqbal Qeis; Siriporn Maneechukate (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2024)
Smong is a folklore from Simeulue Island in the western part of Indonesia. Smong contains wisdom about disaster preparedness and mitigation related to earthquakes and tsunamis. Although located near the epicenter of the earthquake, the inhabitants of Simeulue Island managed to save themselves when the 2004 Indian Ocean earthquake and tsunami disaster occurred through the local wisdom taught in the form of Smong folklore. As Indonesia sits in an earthquake and tsunami-prone area, the local wisdom of the inhabitants of Simeulue Island needs to be widely disseminated as a form of disaster preparedness. However, Smong is taught using the Devayan Language indigenous to Simeulue Island. Therefore, there is a need to adapt this into a modern platform so it can be understood throughout the nation, especially by the younger generation as an early guide for emergency preparedness. This article will discuss the process of adapting the folklore “Smong” into a child-friendly digital media in the form of animation for Indonesian society. The adaptation used the design thinking method through a double-diamond approach which consists of Discover, Define, Develop, and Deliver. The adaptation resulted in an animated film depicting the local wisdom from Simeulue Island accompanied by a song in the Indonesian language so it can be understood and becomes a medium of learning for the child about disaster preparedness related to earthquakes and tsunamis.